The implementation and impacts of the Comprehensive Care Standard in Australian acute care hospitals: a survey study - Beibei Xiong; Christine Stirling; Daniel X. Bailey; Melinda Martin-Khan (BMC, 2024)
Abstract Background Comprehensive care (CC) is becoming a widely acknowledged standard for modern healthcare as it has the potential to improve health service delivery impacting both patient-centred care and clinical outcomes. In 2019, the Australian Commission on Safety and Quality in Health Care mandated the implementation of the Comprehensive Care Standard (CCS). However, little is known about the implementation and impacts of the CCS in acute care hospitals. Our study aimed to explore care professionals' self-reported knowledge, experiences, and perceptions about the implementation and impacts of the CCS in Australian acute care hospitals. Methods An online survey using a cross-sectional design that included Australian doctors, nurses, and allied health professionals in acute care hospitals was distributed through our research team and organisation, healthcare organisations, and clinical networks using various methods, including websites, newsletters, emails, and social media platforms. The survey items covered self-reported knowledge of the CCS and confidence in performing CC, experiences in consumer involvement and CC plans, and perceptions of organisational support and impacts of CCS on patient care and health outcomes. Quantitative data were analysed using Rstudio, and qualitative data were analysed thematically using Nvivo. Results 864 responses were received and 649 were deemed valid responses. On average, care professionals self-reported a moderate level of knowledge of the CCS (median = 3/5) and a high level of confidence in performing CC (median = 4/5), but they self-reported receiving only a moderate level of organisational support (median = 3/5). Only 4% (n = 17) of respondents believed that all patients in their unit had CCS-compliant care plans, which was attributed to lack of knowledge, motivation, teamwork, and resources, documentation issues, system and process limitations, and environment-specific challenges. Most participants believed the CCS introduction improved many aspects of patient care and health outcomes, but also raised healthcare costs. Conclusion Care professionals are confident in performing CC but need more organisational support. Further education and training, resources, multidisciplinary collaboration, and systems and processes that support CC are needed to improve the implementation of the CCS. Perceived increased costs may hinder the sustainability of the CCS. Future research is needed to examine the cost-effectiveness of the implementation of the CCS.